Precurrent self-prompting operants in children: “Remembering” - Parsons, Joseph A. (1981)
In Experiment I, one of three forms of collateral behavior was trained: Differential collateral behavior specific in form to one of two discriminative stimuli; Common collateral behavior of a single form regardless of the stimulus; or Nondifferential collateral behavior of either form regardless of the stimulus. Children were next given a short-delay matching-to-sample task in which the discriminative stimuli served as samples, and the children's previously trained collateral behavior terminated the delay and presented the comparison stimuli. Subjects engaging in sample-specific collateral behavior immediately acquired matching. Subjects engaging in sample-nonspecific collateral behavior failed to acquire matching or did so gradually. In Experiment II the minimal delay in the matching task was varied in a mixed sequence, first with collateral behavior required, and then with collateral behavior prohibited. When emitting collateral behavior Common and Nondifferential subjects showed delay-related decrements in matching while Differential subjects did not. When not emitting collateral behavior all subjects showed delay-related decrements in matching. Common and Nondifferential subjects matched more accurately when prohibited from emitting collateral behavior. Differential subjects matched more accurately when emitting collateral behavior. The results accord with Skinner's (1953, 1968) analysis of precurrent operants.